Multiple cylindrical interface cracks in FGM coated cylinders under torsional transient loading. (October 2018) - Noroozi, M.; Ghassemi, A.; Atrian, A.; Vahabi, M.
Highlights: We solve problem of Somigliana-type dynamic rotational dislocation in FGM coated cylinder. We use the dislocation distribution technique for analysis of multiple cylindrical interface cracks. Nonhomogeneity constant has an efficient effect on DSIFs. FGM layer thickness and crack length have also a crucial effect on DSIFs. Abstract: In the present study, the problem of multiple cylindrical interface cracks between a homogeneous circular cylinder and its functionally graded materials (FGM) coating under torsional impact loading is investigated. First, by using the Laplace and complex Fourier transforms, the solution for Somigliana-type dynamic rotational ring dislocation in a cylinder and its coating is obtained. Next, the distributed dislocation technique is employed to derive a set of Cauchy singular integral equations for multiple cylindrical interface cracks situated between the isotropic cylinder and its FGM coating. These integral equations are solved by Erdogan's collocation method; the dislocation densities on the faces of the cracks are obtained, and the results are used to determine dynamic stress intensity factors (DSIFs). Several examples are provided to study the influences of material nonhomogeneity constant, the FGM layer thickness and crack geometry configuration on the DSIFs at the tips of cracks and, the interaction between the cracks.